Distribution of Crenarchaeota Representatives in Terrestrial Hot Springs of Russia and Iceland - Perevalova, Anna A.; Kolganova, Tatiana V.; Birkeland, Nils-Kåre; Schleper, Christa; Bonch-Osmolovskaya, Elizaveta A.; Lebedinsky, Alexander V. (Applied and Environmental Microbiology, 2008)
ABSTRACT Culture-independent (PCR with Crenarchaeota- specific primers and subsequent denaturing gradient gel electrophoresis) and culture-dependent approaches were used to study the diversity of Crenarchaeota in terrestrial hot springs of the Kamchatka Peninsula and the Lake Baikal region (Russia) and of Iceland. Among the phylotypes detected there were relatives of both cultured (mainly hyperthermophilic) and uncultured Crenarchaeota . It was found that there is a large and diverse group of uncultured Crenarchaeota that inhabit terrestrial hot springs with moderate temperatures (55 to 70°C). Two of the lineages of this group were given phenotypic characterization, one as a result of cultivation in an enrichment culture and another one after isolation of a pure culture, “ Fervidococcus fontis ,” which proved to be a moderately thermophilic, neutrophilic (optimum pH of 6.0 to 7.5), anaerobic organotroph.